Serbia : Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2015)
This Systematic Country Diagnostic (SCD) aims to identify the major constraints on and opportunities for sustaining poverty reduction and shared prosperity in Serbia. The SCD serves as the analytic foundation on which the World Bank Group and the Government of Serbia will define a new Country Partnership Framework for FY2016 to FY2020. It is based on the best possible analysis, drawing on available evidence, and not limited to areas where the World Bank Group is currently engaged. The SCD is structured as follows: Chapter 2 presents the political and economic context. The economic context describes recent trends in growth, shared prosperity, and poverty reduction and briefly discusses factors behind them. Chapter 3 discusses pre-crisis patterns of growth and opportunities for future growth and inclusion in Serbia. Chapter 4 presents drivers of economic growth in Serbia and the principal constraints on growth and competitiveness. Chapter 5 discusses drivers of and constraints to economic inclusion. Chapter 6 outlines risks to sustainable shared prosperity and poverty reduction. Chapter 7 presents priorities for action.